2021
DOI: 10.5534/wjmh.210055
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Endothelial Dysfunction Can Cause Erectile Dysfunction: Histopathological, Immunohistochemical, and Ultrastructural Study of the Human Penis

Abstract: Purpose A pilot study to describe histopathological features of penile tissue of patients who recovered from symptomatic COVID-19 infection and subsequently developed severe erectile dysfunction (ED). Materials and Methods Penile tissue was collected from patients undergoing surgery for penile prosthesis for severe ED. Specimens were obtained from two men with a history of COVID-19 infection and two men with no history of infection. Specimens were imaged with TEM and H&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
133
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(145 citation statements)
references
References 5 publications
4
133
1
7
Order By: Relevance
“…In particular, there are scarce data about the long-term persistent complications in the endocrine (outside of diabetes), gynecologic, obstetric, and rheumatologic systems. Some case reports on potential sexual dysfunction (eg, erectile dysfunction, anorgasmia) have been reported, but there is yet to be conclusive data on whether these conditions persist more than 4 weeks ( 184 , 185 ). Emerging data regarding POTS, myalgia encephalomyelitis/chronic fatigue syndrome, gastrointestinal complications, and others will need to be substantiated with greater follow-up of patients over time.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there are scarce data about the long-term persistent complications in the endocrine (outside of diabetes), gynecologic, obstetric, and rheumatologic systems. Some case reports on potential sexual dysfunction (eg, erectile dysfunction, anorgasmia) have been reported, but there is yet to be conclusive data on whether these conditions persist more than 4 weeks ( 184 , 185 ). Emerging data regarding POTS, myalgia encephalomyelitis/chronic fatigue syndrome, gastrointestinal complications, and others will need to be substantiated with greater follow-up of patients over time.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study can be seen in line with the aetiopathological mechanisms relating ED, endothelial disease and COVID‐19 together (Sansone et al, 2021 ). Furthermore, a very recent study had detected COVID‐19 virus in the penis after initial infection in humans as well as widespread endothelial cell dysfunction from COVID‐19 infection (Kresch et al, 2021 ). The present study had demonstrated significant differences in serum testosterone between cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Another study reported on histopathological, immunohistochemical, and ultrastructural findings on penile tissue of COVID-19 patients. The authors have demonstrated the presence of the COVID-19 virus in the penis long after the initial infection in humans and suggest that widespread endothelial cell dysfunction from COVID-19 infection can contribute to ED [ 16 ].…”
Section: Introductionmentioning
confidence: 99%